2010
DOI: 10.2174/156800910791517172
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR Pathway: A New Target in Cancer Therapy

Abstract: Mammalian target of rapamycin (mTOR) is a key protein kinase controlling signal transduction from various growth factors and upstream proteins to the level of mRNA translation and ribosome biogenesis, with pivotal regulatory effects on cell cycle progression, cellular proliferation and growth, autophagy and angiogenesis. The mTOR pathway, and its upstream regulators in the PI3K/PTEN/AKT cascade, are altered in a variety of experimental and human malignancies.This has led to the prediction that mTOR inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 0 publications
2
127
0
Order By: Relevance
“…Under normal cellular conditions, PTEN is a negative regulator of tumorigenic activity; however, when lost or inactivated, the PI3K/ Akt/mTOR pathway is enhanced. As such, loss of PTEN can be an indicator of aggressive behavior in tumors of various cell types (6). In our present study, we found that that the status of PTEN expression inversely correlates with sunitinib resistance in renal and prostate cancer cells.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Under normal cellular conditions, PTEN is a negative regulator of tumorigenic activity; however, when lost or inactivated, the PI3K/ Akt/mTOR pathway is enhanced. As such, loss of PTEN can be an indicator of aggressive behavior in tumors of various cell types (6). In our present study, we found that that the status of PTEN expression inversely correlates with sunitinib resistance in renal and prostate cancer cells.…”
Section: Introductionsupporting
confidence: 68%
“…One possible mechanism implicated in TKI resistance may be the constitutive activation of various intracellular pro-tumorigenic pathways downstream of receptor signaling. Activation of the PI3K/Akt/mTOR pathway, chiefly due to redundant autocrine signaling rather than mutations, is clearly involved in tumor initiation and progression (6). The PI3K/Akt/mTOR axis is a central crossroad of many intracellular signaling pathways, exhibiting direct and indirect control over a multitude of cellular events including cell cycle progression, cellular proliferation/growth, autophagy, and angiogenesis (6).…”
Section: Introductionmentioning
confidence: 99%
“…This pathway regulates numerous survival and proliferation networks in the cell; therefore, its inhibition not only activates autophagy but also cell cycle arrest and/or apoptosis [74]. Specific mTOR inhibitors have been developed and validated, and two of them (Everolimus and Temsirolimus) are now approved for the treatment of renal cell carcinoma and mantle cell lymphoma [75]. Everolimus indeed induces massive autophagy in vivo, with reduced tumoral mass, for example in leukemia [76], in advanced pancreatic tumors [77] and in many other tumors [78].…”
Section: To Provoke Cell Deathmentioning
confidence: 99%
“…There is a suggestion that phosphorylated mTOR expression is a poor prognostic marker because it has been associated with worse disease-free survival in a small cohort [117]. Various cancers demonstrate abnormalities in mTOR or in its upstream regulators, such as PI3K, phosphatase and tensin homolog, and AKT; therefore, specific inhibitors of mTOR have been investigated as targeted cancer therapies [112,114].…”
Section: Mammalian Target Of Rapamycinmentioning
confidence: 99%